Modeling stream flow and sediment yield using the SWAT model: a case study of Ankara River basin, Turkey. (4th May 2018) - Duru, Umit; Arabi, Mazdak; Wohl, Ellen E.
Abstract: The Soil and Water Assessment Tool (SWAT) was tested for prediction of stream flow and sediment yield in the Ankara basin, Turkey. The overall objective of this study was to evaluate the performance and applicability of the SWAT and generate a soil erosion map. Thirteen years of daily/monthly flow and monthly sediment data were used for calibration and validation. Model performance was evaluated using statistical measures to assess the applicability of the model in simulating stream flow and sediment yield during calibration (1989–1996) and validation (1982–1984) periods. Nash Sutcliffe efficiency (NSE), relative error (RE), and R² (coefficient of determination) for daily flow were computed as 0.61, −0.55, and 0.78, respectively; and as 0.79, −0.58, and 0.89 for monthly flow during the calibration. Statistical comparisons of sediment yield produced values for NSE, RE, and R² of 0.81, −1.55, and 0.93, respectively, during the calibration. The resulting map suggests that significant portions of urbanized and highly cultivated areas in the vicinity of stream channels are particularly vulnerable to soil erosion. SWAT satisfactorily simulated hydrology and sediment yield and can be used as a tool in decision-making for water resources planning in a basin with similar characteristics.